Development of Four-tier Multiple-choices Test to Diagnose Student's Misconception - Prabowo, Anggit; Herman, Tatang; Fatimah, Siti; Ahniah, Arum Dwi (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
Studies in Indonesia delineate that junior high school students in Indonesia have low mastery of circle material. Students with low mastery of the material tend to have misconceptions. The goal of this study is to develop a four-tier diagnostic test for circle material to identify the level of their understanding, including misconception in circle material. This development used the ADDIE model. It comprises four phases: Analysis, Design, Development, Implementation, and Evaluation. The test developed consists of 20 items which four experts in learning mathematics have validated. They are two lecturers and two teachers of mathematics who have teaching experience of more than ten years. The validated test was implemented on 34 grade 8 students in Yogyakarta. From the test results obtained information, of the 20 test items, on average, have an ideal difficulty level. All items have a good discriminant index. Test reliability was estimated using the Cronbach Alpha formula. The estimation results show a test reliability coefficient of 0.72. Students as test respondents stated that the tests developed contained easy-to-understand instructions, easy-to-understand language, sufficient test time, clear pictures, and enough items. This test can help junior high school mathematics teachers in Indonesia to identify their students' misconceptions and level of understanding, especially regarding circle material.Hasil-hasil studi menunjukkan siswa sekolah menengah pertama di Indonesia memiliki penguasaan yang rendah pada materi lingkaran. Siswa dengan penguasaan materi yang rendah terindikasi mengalami miskonsepsi. Penelitian ini bertujuan untuk mengembangkan tes diagnostik tipe four-tier pada materi lingkaran untuk mendiagnosis level pemahaman siswa pada materi lingkaran, termasuk miskonsepsi yang dialami siswa. Pengembangan ini menggunakan model ADDIE (Analysis, Design, Devalopment, Implementation, Evaluation). Tes yang dikembangkan terdiri atas 20 butir yang telah divalidasi oleh 4 orang ahli dalam pembelajaran matematika yang terdiri atas 2 orang dosen pembelajaran matematika dan 2 orang guru matematika yang memiliki pengalaman mengajar lebih dari 10 tahun. Tes yang sudah divalidasi diujicobakan kepada 34 siswa kelas 8 di Yogyakarta. Dari hasil uji coba didapat informasi bahwa dari 20 butir soal tes rata-rata memiliki tingkat kesukaran yang ideal. Keseluruhan butir memiliki daya pembeda yang baik. Keandalan tes diestimasi dengan menggunakan formula Cronbach Alpha. Hasil estimasi menunjukkan koefisien reliabilitas tes sebesar 0,72. Siswa sebagai responden uji coba menyatakan bahwa tes yang dikembangkan memuat petunjuk yang mudah dimengerti, bahasa yang mudah dipahami, waktu tes yang cukup, gambar yang jelas, dan jumlah butir soal yang cukup. Tes yang dikembangkan ini dapat membantu guru matematika sekolah menengah pertama di Indonesia untuk mengidentifikasi miskonsepsi dan level pemahaman siswanya, khususnya pada materi lingkaran.